Pregunta
upstudy study bank question image url

Solve the following equation completely. There are 3 answerboxes listed. \( x^{3}+2 x^{2}-2 x-4=0 \)

Ask by Rowe Moreno. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are: - x = -2 - x = √2 - x = -√2

Solución

We start with the equation:   x³ + 2x² - 2x - 4 = 0 Step 1. Look for a rational root using the Rational Root Theorem. Test x = -2:   (-2)³ + 2(-2)² - 2(-2) - 4 = -8 + 8 + 4 - 4 = 0 So, x = -2 is a root. Step 2. Factor the polynomial by dividing by (x + 2). Dividing:   x³ + 2x² - 2x - 4 ÷ (x + 2) Use synthetic division with -2:   Coefficients: 1 2 -2 -4   Bring down 1.   Multiply 1 by -2 = -2; add to 2 gives 0.   Multiply 0 by -2 = 0; add to -2 gives -2.   Multiply -2 by -2 = 4; add to -4 gives 0. The quotient is: x² + 0x -2, which simplifies to x² - 2. Step 3. Solve the quadratic factor:   x² - 2 = 0  ⟹  x² = 2  ⟹  x = √2 or x = -√2 Thus, the complete solution set is: Answerbox 1: x = -2 Answerbox 2: x = √2 Answerbox 3: x = -√2

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( x^{3}+2 x^{2}-2 x-4=0 \), let's first look for possible rational roots using the Rational Root Theorem. Testing small integers, we find that \( x = 1 \) is a root. Now we can perform synthetic division to divide the polynomial by \( x - 1 \): ``` 1 | 1 2 -2 -4 | 1 3 1 -------------------- 1 3 1 -3 ``` This gives us the quotient \( x^2 + 3x + 4 \) and a remainder of \( 0 \). Thus, we can factor our original polynomial as: \[ (x - 1)(x^2 + 3x + 4) = 0 \] Next, we need to solve the quadratic \( x^2 + 3x + 4 = 0 \) using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Here, \( a = 1, b = 3, c = 4 \): \[ x = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 1 \cdot 4}}{2 \cdot 1} = \frac{-3 \pm \sqrt{9 - 16}}{2} = \frac{-3 \pm \sqrt{-7}}{2} \] This gives us complex roots: \[ x = \frac{-3}{2} \pm \frac{\sqrt{7}}{2}i \] Thus, the complete list of solutions for the equation \( x^{3}+2 x^{2}-2 x-4=0 \) is: 1. \( x = 1 \) 2. \( x = \frac{-3}{2} + \frac{\sqrt{7}}{2}i \) 3. \( x = \frac{-3}{2} - \frac{\sqrt{7}}{2}i \) So, the complete answer boxes will be: 1. \( 1 \) 2. \( \frac{-3}{2} + \frac{\sqrt{7}}{2}i \) 3. \( \frac{-3}{2} - \frac{\sqrt{7}}{2}i \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad